2023
DOI: 10.3390/ijms24108498
|View full text |Cite
|
Sign up to set email alerts
|

Role of Senescent Astrocytes in Health and Disease

Abstract: For many decades after their discovery, astrocytes, the abundant glial cells of the brain, were believed to work as a glue, supporting the structure and metabolic functions of neurons. A revolution that started over 30 years ago revealed many additional functions of these cells, including neurogenesis, gliosecretion, glutamate homeostasis, assembly and function of synapses, neuronal metabolism with energy production, and others. These properties have been confirmed, limited however, to proliferating astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…External stimuli polarize microglia towards a proinflammatory phenotype, activating inflammation, oxidative stress, and cytotoxicity, leading to neuronal death [ 62 ]. Astrocytes, the most abundant and diverse glial cells in the CNS, engage in the neurotransmitter metabolic processes (Glu, ATP, and GABA), and communication with neurons through neurotransmitters and neuromodulators, forming “tripartite synapses” [ 63 , 64 ]. Proinflammatory microglia release various mediators, triggering reactive astrocyte transformation and neuroinflammatory cascades [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…External stimuli polarize microglia towards a proinflammatory phenotype, activating inflammation, oxidative stress, and cytotoxicity, leading to neuronal death [ 62 ]. Astrocytes, the most abundant and diverse glial cells in the CNS, engage in the neurotransmitter metabolic processes (Glu, ATP, and GABA), and communication with neurons through neurotransmitters and neuromodulators, forming “tripartite synapses” [ 63 , 64 ]. Proinflammatory microglia release various mediators, triggering reactive astrocyte transformation and neuroinflammatory cascades [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes, the most abundant cell type in the brain, play crucial roles in maintaining brain homeostasis. 46 Recent studies indicated that activated microglia can convert astrocytes into the neurotoxic A1 phenotype via the secretion of IL‐1α, TNF‐α, and C1q, and dysfunction of astrocytes critically impacts neuronal survival in various neurological diseases. 47 , 48 , 49 , 50 Previous studies, including our own, have demonstrated that DEX treatment effectively reduces microglial activation and subsequent neuroinflammation, improving neurological outcomes in neonatal rodents following HIBD.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes, the most abundant glial cells within the CNS implicated in glutamate homeostasis and neurogenesis processes, are the metabolic and energetic support of neurons and are involved in synapse assembly and function, forming part of the tripartite synapse, among many other functions. During aging, these cells undergo changes in gene expression, leading to the appearance of senescent forms of astrocytes [ 76 ]. In contrast, microglial cells are the specific macrophages of the CNS that are specialized in phagocytizing apoptotic neurons, eliminating aggregated extracellular proteins, defending against infections, and pruning synapses, among other functions [ 77 ].…”
Section: Aging and Its Connection To Nrf2mentioning
confidence: 99%